2014
DOI: 10.3233/jad-132738
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and Oxidative Stress in Neurodegenerative Diseases

Abstract: Neurodegenerative disorders affect almost 30 million individuals leading to disability and death. These disorders are characterized by pathological changes in disease-specific areas of the brain and degeneration of distinct neuron subsets. Despite the differences in clinical manifestations and neuronal vulnerability, the pathological processes appear similar, suggesting common neurodegenerative pathways. Apoptosis seems to play a key role in the progression of several neurologic disorders like Alzheimer's dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
318
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 532 publications
(334 citation statements)
references
References 158 publications
10
318
0
6
Order By: Relevance
“…The most common and well-defined form of programmed cell death is apoptosis, which is a physiological cell-suicide pro-gramme that is essential for embryonic development (Campos-Ortega and Hartenstein, 2013), immune-system function (Abbas et al, 2012) and the maintenance of tissue homeostasis (Sonnenberg et al, 2011) in multi-cellular organisms. Deregulation of apoptosis has been implicated in numerous pathological conditions, including neurodegenerative diseases (Radi et al, 2014), autoimmunity and cancer (Rabinovich and Croci, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The most common and well-defined form of programmed cell death is apoptosis, which is a physiological cell-suicide pro-gramme that is essential for embryonic development (Campos-Ortega and Hartenstein, 2013), immune-system function (Abbas et al, 2012) and the maintenance of tissue homeostasis (Sonnenberg et al, 2011) in multi-cellular organisms. Deregulation of apoptosis has been implicated in numerous pathological conditions, including neurodegenerative diseases (Radi et al, 2014), autoimmunity and cancer (Rabinovich and Croci, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged episodes of oxidative stress produces an excessive accumulation of reactive oxygen species (ROS), capable of inducing deleterious cellular and biomolecular damage to the host [1][2][3][4][5]. Neurons are particularly sensitive to ROSmediated, oxidative damage, as they contain higher numbers of mitochondria along their cell bodies and axonal/dendritic tree lengths, compared to other cell types.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress is implicated in the onset, progression and pathogenesis of numerous diseases and conditions, including periodontal disease, neurodegeneration and ageing [1][2][3][4][5][6][7][8]. Prolonged episodes of oxidative stress produces an excessive accumulation of reactive oxygen species (ROS), capable of inducing deleterious cellular and biomolecular damage to the host [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, enhanced levels of OTS have been reported in the mice brain with apolipoprotein E deficiency exposed to concentrated ambient NPs (25). High prevalence of neurodegenerative diseases such as Alzheimer's disease and primary brain tumors has been reported, however, the exact etiology of them is not clear yet and OTS has been reported as a possible mechanism of such diseases (26)(27)(28)(29).…”
Section: Evidence Acquisitionmentioning
confidence: 99%
“…The high surface activity of NPs concentrated in the brain, during long-term exposures, may be related to cellular interactions and free radical formation leading to brain damage and increased risk of neurodegenerative conditions (25). Because of the high level of a metabolic rate, low endogenous scavenger levels, and extensive networks of neurons, the brain is more vulnerable to OTS than many other tissues (28). It has been reported that excessive accumulation of ROS resulted in irreversible neuronal death in the brain which may progress to develop neurodegenerative disorders (69).…”
Section: Iron Oxide Nanoparticlesmentioning
confidence: 99%